2021
DOI: 10.1038/s41598-021-90761-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of the intestinal mucosa and immune cells of the colon by multi-parametric histological techniques

Abstract: The impact of the post-mortem interval (PMI) on the optical molecular characteristics of the colonic mucosa and the gut-associated lymphoid tissue (GALT) were examined by multi-parametric measurements techniques. Inflammatory cells were identified by immunohistochemical staining. Molecular parameters were estimated using the Raman spectroscopy (RS) and Fourier Transform Infrared (FTIR) spectroscopic imaging. The 3D refractive index (3D-RI) distributions of samples were determined using the digital holographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Protein synthesis is one of the most complicated biochemical processes undertaken by the cell, requiring approximately 150 different polypeptides and 70 different RNAs. In addition, protein synthesis can be stopped when only a small fraction of the ribosome is inactivated by certain ribotoxins or when kinases associated with oxidative stress are activated . The comparison between untreated human colon cells and cancer human colon cells upon statin supplementation shows that adding of statins effectively decreases the cell’s protein level (the ratios 1004/1258 and 1004/1658 increase), especially for a longer incubation time of 48 h. One can see from Figure that the strongest effect was observed for simvastatin.…”
Section: Discussionmentioning
confidence: 96%
“…Protein synthesis is one of the most complicated biochemical processes undertaken by the cell, requiring approximately 150 different polypeptides and 70 different RNAs. In addition, protein synthesis can be stopped when only a small fraction of the ribosome is inactivated by certain ribotoxins or when kinases associated with oxidative stress are activated . The comparison between untreated human colon cells and cancer human colon cells upon statin supplementation shows that adding of statins effectively decreases the cell’s protein level (the ratios 1004/1258 and 1004/1658 increase), especially for a longer incubation time of 48 h. One can see from Figure that the strongest effect was observed for simvastatin.…”
Section: Discussionmentioning
confidence: 96%
“…The samples used to estimate the PMI came from different organs, such as brain [ 38 , 39 , 42 ], thyroid [ 35 , 36 ], pancreas [ 34 , 37 , 38 ], gingival tissue [ 14 , 27 ], skin [ 44 ], heart [ 33 , 43 ], large intestine [ 45 ], female genital system [ 46 ], bone marrow [ 40 ], skeletal muscle [ 41 ], as well as lung and liver [ 42 ]. For these tissues, the various authors used different markers, without any overlap or repetition ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zadka et al [ 45 ] found that a significant reduction in the antigenic expression of CD4 and especially CD8 lymphocyte T markers occurred in the intestinal mucosa of eight cadavers with a PMI between 2 and 7 days. However, IHC expression of CD3 and CD45 did not show statistically significant changes in their study.…”
Section: Resultsmentioning
confidence: 99%
“…Protein synthesis is one of the most complicated biochemical processes undertaken by the cell, requiring approximately 150 different polypeptides and 70 different RNAs. In addition protein synthesis can be stopped when only a small fraction of the ribosome is inactivated by certain ribotoxins or when kinases associated with oxidative stress are activated [54]. The comparison between untreated human colon cells and cancer human colon cells upon statins supplementation shows that adding of statins effectively decreases the cell's proteins level (the ratios 104/1258, 1004/1658 increase) especially for longer incubation time of 48h.…”
Section: Figure 2 Raman Band Intensities Ratios For Selected Raman Ba...mentioning
confidence: 99%